Sensory quality of wine: quality assessment by merging ranks of an expert‐consumer panel. (4th June 2017) - De Mets, G.; Goos, P.; Hertog, M.; Peeters, C.; Lammertyn, J.; Nicolaï, B.M.
Abstract: Background and Aims: Despite being a major focus in wine production, there are currently no standard procedures to measure the overall sensory quality of wine. Ratings from specialised guides and magazines, while abundant, lack scientific and statistical foundation and may confound preference with intrinsic quality. The method presented aims to bridge this gap by providing a 'quality assessment by merging ranks of an expert consumer panel (QAMREC)' procedure, which ranks wines on a quantitative scale according to their sensory quality. Methods and Results: The methodology is essentially a preference testing method, however, by confining the sample space to wines with a similar origin and vinification and the recruitment of an expert panel, the effect of individual differences in preference can be reduced and the resulting ranking is believed to provide a better representation of the intrinsic quality of wines as valued by educated consumers who use an unconscious rationale for their judgement. It also takes into account human limitations and organisational constraints. Expert consumers, consumers familiar with the rating of the sensory characteristics of wine, were selected as panellists with well‐defined criteria including a high wine involvement profile. An optimised incomplete block design was deployed to guarantee a balanced tasting sequence. By applying the rank‐order logit model, incomplete rankings obtained were converted into utility values for each wine compared with a reference wine. These utility values are an approximation of the intrinsic quality of the individual wines as judged by experts. The method was applied in ten tasting sessions each comprising nine wines from one particular origin and 12 panellists. Most sessions, with the exception of the Pouilly Fumé and the Graves tastings, resulted in the identification of several wines with statistically different utilities. Conclusions: The QAMREC procedure regards the sensory quality of wine as the preference of a wine‐educated population and also meets the required statistical significance for being employed in scientific experiments. Significance of the Study: These findings introduce QAMREC as a valid approach for assessing the sensory quality of wines.